Meningkatkan Kemampuan Berpikir Kritis pada Tema 2 Subtema Udara Bersih bagi Kesehatan dengan Penerapan Strategi Debat Aktif di Kelas V SDN 138 Pekanbaru - Hamzah, Fajar Alam (Lembaga Anotero Scientific, 2022)
This research aims to improve learning outcomes for theme 2 sub-theme clean air for health by implementing active debate strategies in class V at SDN 138 Pekanbaru for the 2021-2022 academic year. This research was carried out on Monday 26 April 2021 in cycle 1 and Wednesday 05 May 2021 in cycle 2. The subjects in this research were 26 class V students at SDN 138 Pekanbaru, 12 female students and 14 male students. The data collection techniques used in this research are observation, test and documentation techniques. Based on the research results, it was found that in cycle 1 there were 69.2% of students who had completed it and 30.8% of them had not completed it, there were 8 students, for cycle 2 there were 100% of students who had completed it, namely all 26 students.